Connectedness on Intuitionistic Fuzzy Soft Topological Spaces - Serkan Karataş; Mehmet Akif İşleyen (Journal of New Theory)
In this study, we introduce intuitionistic fuzzy soft connected sets in intuitionistic fuzzy soft topological spaces and some properties. Moreover, we extend the notion of Ci connectedness (i = 1, 2, 3, 4) to intuitionistic fuzzy soft topological spaces.